Donor desmopressin treatment does not affect transplant outcome in the Fischer to Lewis rat renal transplant model - Mundt, Heiko; Höger, Simone; Waldherr, Rüdiger; Schnülle, Peter; Krämer, Bernhard; Yard, Benito A.; Göttmann, Uwe; Benck, Urs Tobias (Experimental and clinical transplantation, 2016)
Objectives: Retrospective studies suggest that donor desmopressin (DDAVP) treatment improves renal transplant outcome. The present study tests the hypothesis that desmopressin neutralizes the graft's endothelium from proinflammatory angiopoietin 2 containing Weibel-Palade bodies in the donor, resulting in reduced Weibel-Palade body release at the time of reperfusion in the recipient. Materials and Methods: Using rat models, we examined the influence of desmopressin treatment on the expression of vasopressin 2 receptors and adhesion molecules in brain-dead donors, with renal function examined in allogeneic recipients. The influence of desmopressin on the expression of adhesion molecules also was tested in vitro. Results: Vasopressin 2 receptors were restricted to collecting ducts and distal tubules and only scarcely found in the renal vasculature. Vasopressin 2 receptor expression was down-regulated in brain-dead rats by desmopressin. Renal expression of vascular cellular adhesion molecule 1 and intercellular adhesion molecule 1 were significantly reduced in these rats. In contrast, angiopoietin 2 did not influence the expression of adhesion molecules in in vitro cultured endothelial cells after tumor necrosis factor α stimulation. Donor desmopressin treatment improved neither renal function nor histology in allogeneic renal transplant recipients. Conclusions: Our data do not support the hypothesis that the clinically observed salutary effect of desmopressin is mediated by depletion of Weibel-Palade bodies in renal allografts.